2015
DOI: 10.15713/ins.jmrps.37
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of serum iron and protein levels in oral submucous fibrosis: A clinical research

Abstract: Background: Oral submucous fibrosis (OSMF) is a potentially malignant oral condition which shares a unique predisposition of occurrence in the Indian subcontinent, parts of Asia and among individuals of the Indian origin abroad and continues to rise in incidence between younger and older people. Therefore, early detection of the disease can serve as the best available tool and can play a significant role in providing effective treatment at the appropriate time and thus preventing it from malignant transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…[33]. Other studies conducted by Saurabh et al [34], Kode et al [17] and Tadakamadla et al [30] were also found consistent. The difference in serum iron levels in the present study and Indian studies is due to the difference in the type of diet intake as Indians preferred vegetarian diet as compared to the non vegetarian diet which is common in the society.…”
Section: Discussionsupporting
confidence: 66%
“…[33]. Other studies conducted by Saurabh et al [34], Kode et al [17] and Tadakamadla et al [30] were also found consistent. The difference in serum iron levels in the present study and Indian studies is due to the difference in the type of diet intake as Indians preferred vegetarian diet as compared to the non vegetarian diet which is common in the society.…”
Section: Discussionsupporting
confidence: 66%
“…[ 8 9 10 11 ] There are also studies only on protein estimation. [ 12 13 14 15 16 17 ] However, there are not any studies which correlate functional, clinical, and histopathological grading with total protein estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the TSP level in the serum of OSMF patients was found to be significantly higher than that of normal individuals. [ 14 15 16 17 18 20 ]…”
Section: Discussionmentioning
confidence: 99%